Joint stiffness analysis and optimization as a mechanism for improving the structural design and performance of a vehicle. (May 2014) - Kiani, Morteza; Motoyama, Keiichi; Rais-Rohani, Masoud; Shiozaki, Hirotaka
An approach is presented to evaluate the structural performance of a vehicle model in terms of the joint stiffness. Seven major joints on the left and right sides of the vehicle body are identified, and each joint is decomposed in the finite element model and assigned a separate set of material properties. By adjusting the elastic modulus of each structural member, the effects of the joint stiffness on the full and offset frontal impacts as well as the vibration characteristics are examined. Latin hypercube sampling is used in the design of experiments to approximate the acceleration, the intrusion distance, and the fundamental vibration frequencies using full quadratic polynomial response surface models. Through direct differentiation, the sensitivities of the crash responses and the vibration responses to the joint stiffness are calculated. A constrained multi-objective optimization problem is formulated and solved to improve the structural responses by adjusting the stiffness at each joint. Evaluation of the car body structure based on the optimum joint stiffness showed a superior performance relative to the baseline model without a weight penalty. The results of both the sensitivity analysis and the design optimization are presented and discussed.